Keikhlasan Maria sebagai Model Kemuridan Gereja di Tengah Krisis Iman Menurut Kitab Wahyu 12:4b-6 - Ma, Ferdianus Gato; Sogen, Christian D.J; Nainaif, Marianus T.; Bani, Rafael; Hepat, Klaudius A.B.R.; Taitoh, Petrus K.; Bouk, Andronikus P.; Wawin, Martinus L.; Senda, Siprianus S. (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The basic vocation of Christian believers as apostles today is to be bearers of God's good news. The joyful word that God sent down to earth through the mission of His Son becomes a continuous message of joy. In the context of social life with all its arrangements and circumstances, believers are called to be salt and light that have a good affect on life together. The form of discipleship of the Church today is a form of discipleship that is ready to carry out the will of God and prioritise the interests of many people. In the context of the Month of Mary, reflection on the virtues of Mary becomes relevant to be able to evaluate the extent to which the faithful live and are responsible for their predicate as children of God. By using a literature research method based on social philosophy and reflection on scriptural theology, the phenomenon of a crisis of faith seen in social inequality is analysed by putting forward ideal ideas that can inspire Christian believers to strive to become members of the Church who affect the good of many people. The results of this analysis are very useful to purify the call of discipleship of believers to sincerely answer God's call and prioritise His will as inspired by John in Revelation 12: 4b-6.